Psicanálise, gênero e singularidade - Knudsen, Patricia Porchat Pereira da Silva [UNESP] (My University, 2013)
Psychology, and more specifically Psychoanalysis have been called to manifest themselves about current phenomena regarding gender and sexuality issues. The demand for acting on these matters has grown, partly due to the influence of media. It is possible to point out limits on the performance of these professionals for lacking a reflection on the concept of subject, the effects of a pathologization of gender and the use of a binary conception of gender.

A Psicologia e, mais especificamente, a Psicanálise vêm sendo chamadas a se manifestar acerca de fenômenos atuais sobre as questões de gênero e sexualidade. A demanda pela atuação diante dessas questões cresceu, em parte, por influência da mídia. É possível apontar limites na atuação desses profissionais por carecerem de uma reflexão sobre a concepção de sujeito que utilizam, dos efeitos de uma patologização de gênero e da utilização de uma concepção binária de gênero.
Keywords: Psychoanalysis; Gender; Sexuality; Transexuality; Psicanálise; Gênero; Transexualidade